t-plasminogen activator inhibitor-1 polymorphism in idiopathic pulmonary arterial hypertension - Katta, Sujana (Medknow Publications, 2008)
AIM: The aim of the present study was to identify the possible genotypic association of 3’UTR Hind III polymorphism of Plasminogen activator Inhibitor-1 (PAI-1) gene with idiopathic pulmonary arterial hypertension (IPAH). BACKGROUND: IPAH is a disorder with abnormally raised mean pulmonary arterial pressure and increase in the resistance to blood flow in pulmonary artery. One of the pathological features seen is development of intraluminal thrombin deposition leading to thrombosis. Plasminogen activator inhibitor-1 is an important inhibitor of the fibrinolytic system; its up-regulation may suppress fibrinolysis and result in an increased risk of thrombosis. METHOD: Blood samples from 54 IPAH patients and 100 healthy voluntary donors were analyzed by PCR-RFLP method for 3’UTR Hind III polymorphism. RESULTS AND DISSCUSSION: A significant association of Hd2 allele with the disease was observed. Raised mean level of right ventricular systolic pressure was observed in the Hd2/Hd2 genotypic patients, strengthening the role of Hd2 allele in the disease progression. Our data suggests an association of Hd2/Hd2 genotype, which may lead to the up-regulation of PAI-1 gene leading to increased levels of PAI-1, which is seen in IPAH. PAI-1 competes with plasminogen activators and hinders the normal mechanism of plasminogen activation system and leads to thrombosis and formation of plexiform lesions in the lung tissue, further strengthening its role in tissue remodeling and disease progression.